2022
DOI: 10.1111/acem.14462
|View full text |Cite
|
Sign up to set email alerts
|

Major adverse cardiac event rates in moderate‐risk patients: Does prior coronary disease matter?

Abstract: Background: Despite negative troponins and nonischemic electrocardiograms (ECGs), patients at moderate risk for acute coronary syndrome (ACS) are frequently admitted.The objective of this study was to describe the major adverse cardiac event (MACE) rate in moderate-risk patients and how it differs based on history of coronary artery disease (CAD).Methods: A secondary analysis of the HEART Pathway implementation study was conducted. This prospective interrupted time-series study accrued adults with possible ACS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Despite the moderate risk stratification there were no serious adverse events in our study, with only two patients undergoing angiography within 30 days, one of whom progressed to PCI; this was despite a follow‐up time to initial cardiac investigation being on average 31 days post ED discharge. Consistent with recent data suggesting a MACE of 1.7% in moderate risk patients with no pre‐existing CAD, 10 this lack of MACE despite a prolonged time to testing suggests that the pathway is relatively safe, although a study of this size was not powered to detect a statistical difference in MACE between the cohorts and this needs confirmation by a larger study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Despite the moderate risk stratification there were no serious adverse events in our study, with only two patients undergoing angiography within 30 days, one of whom progressed to PCI; this was despite a follow‐up time to initial cardiac investigation being on average 31 days post ED discharge. Consistent with recent data suggesting a MACE of 1.7% in moderate risk patients with no pre‐existing CAD, 10 this lack of MACE despite a prolonged time to testing suggests that the pathway is relatively safe, although a study of this size was not powered to detect a statistical difference in MACE between the cohorts and this needs confirmation by a larger study.…”
Section: Discussionsupporting
confidence: 81%
“…NHFA/CSANZ guidelines recommend that further diagnostic imaging be performed on moderate risk patients to provide prognostic information, and that this testing be done during or shortly after discharge from ED 6 with no specific timing suggested. This moderate risk group is, however, a heterogenous group of patients with a risk of MACE somewhere between 2% and 8%, 8–10 10%–20% of whom will already have had previous cardiac imaging, 9 and trying to further delineate risk among the subgroups within this cohort is complex. As such, various management strategies are employed in this group and many of these patients are admitted from the ED for short stay inpatient management, including changes in medical therapy or functional testing.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Academic Emergency Medicine , McGinnis et al 12 provide a novel analysis assessing the impact of a history of coronary artery disease (CAD) on the rate of MACE among patients classified as moderate risk by the HEART Pathway. They found that a reported history of CAD in patients classified as moderate risk conferred an increased risk of MACE compared to those without reported CAD.…”
mentioning
confidence: 99%
“…Recently, with the development of the Heart Pathway's mobile-based application as well as an integrated electronic health record (EHR) clinical decision support (CDS) tool, 10 it has begun to find broader adoption outside its derivation environment. 11 In this issue of Academic Emergency Medicine, McGinnis et al 12 provide a novel analysis assessing the impact of a history of coronary artery disease (CAD) on the rate of MACE among patients classified as moderate risk by the HEART Pathway. They found that a reported history of CAD in patients classified as moderate risk conferred an increased risk of MACE compared to those without reported CAD.…”
mentioning
confidence: 99%